An effective teaching model for special education teachers in Malaysia: the mediating role of personal factors between contextual factors and teaching practices - Abduh, Bungawali; Khairuddin, Khairul Farhah; Zainal, Mohd Syazwan (Frontiers in Education, 2026)
IntroductionEffective teaching plays an important role in improving students’ learning outcomes. Unfortunately, research on factors influencing special education teachers’ effective teaching remains lacking. This study aimed to examine the extent to which perceived personal and school-related contextual factors influence effective teaching practices.MethodsThe study utilized data from a survey involving 311 special education teachers in Malaysian secondary schools to construct structural equation models of the interplay between the teachers’ personal factors, contextual factors, and teaching effectiveness. Data were analyzed using Structural Equation Modelling (SEM). This study also validated the mediation testing by utilizing a resampling procedure known as a bootstrapping method.ResultsThe findings indicated that contextual factors significantly influence the teachers’ beliefs, knowledge, self-efficacy, and attitudes. Specifically, beliefs and knowledge were also found to significantly and directly influence effective teaching practices, as well as serve as full mediators between contextual factors and effective teaching practices.DiscussionHence, this study highlights the need for professional development programs emphasizing teachers’ beliefs and knowledge, particularly to improve effective teaching practices among special education teachers.